2016
DOI: 10.3892/or.2016.4584
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol inhibits STAT3 activation pathway leading to growth suppression and apoptosis induction in human cholangiocarcinoma cells

Abstract: STAT3 plays a significant role in the development of cholangiocarcinoma (CCA) associated with the liver fluke (Opisthorchis viverrini; Ov). Xanthohumol (XN), a prenylated flavonoid extracted from hops, has known anticancer activity and could potentially target STAT3. The present study determined the effect of XN on STAT3, as well as ascertained its usefulness against CCA. The CCA cell proliferation at 20 µM and 50 µM of XN was shown to inhibited, while 20 µM partially inhibited IL-6-induced STAT3 activation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 45 publications
(53 reference statements)
0
31
0
Order By: Relevance
“…These results suggested that XN could reduce expression of CD44v8-10 via the possible mechanism of oxidative damage inhibition (reduction of phospho-p38 MAPK activation). Furthermore, it has been shown that XN could effectively suppress the growth of tumor and induced apoptosis in CCA cells and tumor inoculated mice ( Dokduang et al, 2016 ). Currently, it has been reported that the oxidative stress could induce Wnt activation ( Yoshida & Saya, 2014 ), and then triggered the transcription of CD44 ( Ishimoto et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that XN could reduce expression of CD44v8-10 via the possible mechanism of oxidative damage inhibition (reduction of phospho-p38 MAPK activation). Furthermore, it has been shown that XN could effectively suppress the growth of tumor and induced apoptosis in CCA cells and tumor inoculated mice ( Dokduang et al, 2016 ). Currently, it has been reported that the oxidative stress could induce Wnt activation ( Yoshida & Saya, 2014 ), and then triggered the transcription of CD44 ( Ishimoto et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it reduced ROS formation ( Hartkorn et al, 2009 ) and protection against DNA damage ( Pinto et al, 2012 ). Dokduang et al (2016) reported that XN effectively suppressed the growth of tumor and induced apoptosis in CCA cells and tumor inoculated mice by which inhibiting STAT3 activation due to suppression of the Akt-NFκB signaling pathway. These data suggested that XN has a potential to become a useful new approach for the chemoprevention and/or treatment of CCA.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that administration of Xn orally in drinking water to CCA bearing nude mice reduced tumor growth. Tumor tissues from Xn-treated mice exhibited suppressed tumor growth and increased apoptosis as demonstrated by decreased Ki67 positive cells and increased TUNEL positive cells ( Dokduang et al, 2016 ). However, it was difficult to guarantee the identity among individuals through administration of Xn orally in drinking water.…”
Section: Digestive System Cancersmentioning
confidence: 99%
“…More detailed mechanisms of its cancer preventive action are associated with inhibition of the AKT/NFkB pathway, interruption of JAK/STAT3 and Notch1 signaling, modulation of apoptosis regulators (Bax, Bcl-2, survivin, caspases, poly(ADPribose) polimerase) and cell cycle-related factors (cyclin D1, p53, p21), and reduced expression and secretion of MMP-9 and VEGF, i.e. molecules implicated in the angiogenic switch process (Kim et al, 2013;Pilatova et al, 2010;Dokduang et al, 2016). In addition, XN is able to upregulate the E-cadherin/catenin complex in breast cancer cells and to repress the expression of the CXCR4 chemokine receptor in both breast and colon tumor cells to abolish their metastatic capability Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%